Education for sustainable development (ESD) in the Greek education system (Journal of Applied Learning and Teaching, 2023)
The ecopedagogy movement challenges educators to critically engage, cultivate and appreciate human beings as collective and communal potentials in the struggle to achieve convivial life on Earth (Kahn, 2010). “As a form of critical theory of education, ecopedagogy can work at a meta-level to offer dialectical critiques of environmental education and education for sustainable development” (Kahn, 2008, p. 9). This article examines the implementation of Education for Sustainable Development (ESD) in secondary schools in Greece (Table 1), via a literature review and interviews with educators from secondary schools in Greece.More particularly, this paper refers to the challenges and the needs of the Greek educational system to foster sustainable development education in the educational curriculum, providing contemporary education approaches for its integration. It also aims to reinforce global awareness of the environmental challenges and needs of our times, providing ideas that stakeholders and the government can use to act for a better environmental future.